An Introduction to the Study of Law and the Sacred - A. Gearey (Law Text Culture, 2000)
Law and the Sacred might appear as another one of the couplings that have characterised contemporary legal scholarship. Although it is too soon to say if this coupling represents a new departure, it can at least be distinguished by its passion; by its working through of the sense in which secular, western, law has failed to shake its constitution in the pre-modern. Scholarship in this field locates itself in a movement away from the domination of legal theory by a scientising social theory, or a positivisation of knowledge that rejects the mystery and the beyond in its own self-definition and auto-production. This collection attempts to follow a direction suggested by John Milbank: the relaxation of the pressure of the sacred has not filled the only available space with the steam of the "purely human" (1995: 2). A second characteristic of this scholarship is its critical edge: it could be said that it is provoked by a sense of dis-ease; an awareness that law's claims to order and empire ring hollow. In their various ways, the contributors to this volume are impatient with the claim that the triumph of scientific reason is the only means of describing the social world and the role of law. The essays collected here do not seek to give a definition of the sacred, they merely offer some orientation. Addressing the construction of particular paradigms of philosophy, legal history, theology or sociology, they share a concern with alternative ways of reading, with provocative recoveries of rival traditions. If this suggests an orientation to Critical Legal Studies, it is perhaps more to this movement's 'second wave', with its borrowings from continental philosophy and 'postmodern' theory. A reading of the sacred roots of law suggests a perspective on constructions of the contemporary secular legal order that never properly emerged in the first wave of critical legal thought; a perspective that might prove central to future developments in the field of legal theory.